Louro do Pajeú: uma plataforma digital de memória e contemporaneidade poética. - Nascimento, Antônio Marinho do (2020)
Popular poetry is one of the great cultural manifestations of the Northeast of Brazil and it is intimately marked in the process of anthropological formation in the Northeast, being decisive in the construction of the collective identity of the people, which transformed it into a language of plural scope, used in several situations, including in communication. The city of São José do Egito - PE, in the Sertão do Pajeú, has a natural role in this scenario and the figure of one of its poets, Lourival Batista Patriota, Louro do Pajeú, concentrates a great representativeness and importance. This technical report deals with the construction of the Louro do Pajeú digital platform, a virtual space that unites communication, creativity and computer technology and wishes to integrate memory and contemporaneity, concentrating in a systematic and organized way the collection of Lourival Batista and achievements of the new names of the poetic scene city and region. To this end, the Brazilian School of Communication, born from the theory of Luiz Beltrão, and its concepts of folkcommunication and folkcommunicator, was used as a reference to reaffirm the communicative capacity of this literature as a vector of distribution and cognitive facilitation of information,knowledge, entertainment and content generally. The new collection ideas, brought by names like Alckmar Luiz dos Santos, Marisa Lajolo, Maria da Glória Bordini, Raquel Mattes and Viviane Tessitore, considering the revolution of digital technologies, from concepts such as cyberspace, hypertext, hyperlink and transmedia, guided the organization of historical and documentary research and the conception of how the information will be arranged, connected, organized and freely available on the page. The adequacy of the product to the concept of creative industries, as defined by Howkins, Bessi, Bendassoli, Wood Jr, Jenkins and others, was pursued, as a way of integrating it into the digital scenery of the current economy of creativity and new ways of production, work and communication, resized at the beginning of this century by the knowledge society.